2017
DOI: 10.18632/oncotarget.15446
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase NEDD4 is translationally upregulated and facilitates pancreatic cancer

Abstract: AimTo determine the regulation and function of the neural precursor cell expressed developmentally down regulated protein 4 (NEDD4) in PDAC and to determine its dependency on phosphatase and tensin homolog (PTEN) and PI3K/AKT signaling.MethodsWe investigated the expression of NEDD4 and the tumor suppressor PTEN in normal immortalized human pancreatic duct epithelial cell line and pancreatic adenocarcinoma (PDAC) cell lines. We further evaluated whether RNAi-mediated depletion of NEDD4 can attenuate PDAC cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Among these UPS members, the E3 ubiquitin ligase possesses a high variability of their components and interacts directly with ubiquitin substrates and determines the substrate specificity [17]. Neuronally expressed developmentally downregulated 4 (NEDD4, often known as NEDD4-1), a homologue to E6-AP C-terminus (HECT) family of E3 ubiquitin ligase, plays a critical role in the development and progression of many human cancers [18][19][20][21]. Amodio et al demonstrated that NEDD4 facilitated non-smallcell lung carcinomas (NSCLC) cell lines proliferation through inactivation of PTEN [22].…”
Section: Introductionsmentioning
confidence: 99%
“…Among these UPS members, the E3 ubiquitin ligase possesses a high variability of their components and interacts directly with ubiquitin substrates and determines the substrate specificity [17]. Neuronally expressed developmentally downregulated 4 (NEDD4, often known as NEDD4-1), a homologue to E6-AP C-terminus (HECT) family of E3 ubiquitin ligase, plays a critical role in the development and progression of many human cancers [18][19][20][21]. Amodio et al demonstrated that NEDD4 facilitated non-smallcell lung carcinomas (NSCLC) cell lines proliferation through inactivation of PTEN [22].…”
Section: Introductionsmentioning
confidence: 99%
“…NEDD4 appears to be important in promoting HCC proliferation and spread through the stimulation of the PTEN/PI3K/Akt signaling pathway [ 111 ]. In PANC-1 pancreatic ductal adenocarcinoma (PDAC) cells, NEDD4 depletion suppresses cell growth partially by regulating the PTEN/Akt signaling pathway [ 112 ]. In addition, downregulation of NEDD4 suppresses proliferation of RT4 BCa cells.…”
Section: Nedd4 Functions In Human Cancersmentioning
confidence: 99%
“…TRAF6 is a member of TNF pathway and more direct involvement of TNF signaling has been often linked with these disorders. Deregulation in another E3 ligase namely NEDD4 was observed in different types of cancers [147,148] as well as neuronal hyperactivity and seizures [149]. Interestingly, Imai et al…”
Section: Accepted Articlementioning
confidence: 99%
“…TRAF6 is a member of TNF pathway, and more direct involvement of TNF signaling has been often linked with these disorders. Deregulation in another E3 ligase, namely NEDD4, was observed in different types of cancers [144,145] and neuronal hyperactivity and seizures [146]. Interestingly, Imai et al (2015) have identified a new HECT-type E3 ligase, HERC2 that forms a complex with LRRK2, a key molecule involved in Parkinson's disease pathogenesis, and an adaptor-like protein Neurl4 to promote endosomal recycling of Notch ligand Delta-like 1/Delta to the membrane.…”
Section: Human Disorders Caused By Defective E3-ubiquitin Ligases Inv...mentioning
confidence: 99%